Sex differences in mitochondrial gene expression during viral myocarditis - Damian N. Di Florio; Gabriel J. Weigel; David J. Gorelov; Elizabeth J. McCabe; Danielle J. Beetler; Katie A. Shapiro; Katelyn A. Bruno; Isha Chekuri; Angita Jain; Emily R. Whelan; Gary R. Salomon; Sami Khatib; et al. (Biology of Sex Differences, 2024)
Abstract Background Myocarditis is an inflammation of the heart muscle most often caused by viral infections. Sex differences in the immune response during myocarditis have been well described but upstream mechanisms in the heart that might influence sex differences in disease are not completely understood. Methods Male and female BALB/c wild type mice received an intraperitoneal injection of heart-passaged coxsackievirus B3 (CVB3) or vehicle control. Bulk-tissue RNA-sequencing was conducted to better understand sex differences in CVB3 myocarditis. We performed enrichment analysis and functional validation to understand sex differences in the transcriptional landscape of myocarditis and identify factors that might drive sex differences in myocarditis. Results As expected, the hearts of male and female mice with myocarditis were significantly enriched for pathways related to an innate and adaptive immune response compared to uninfected controls. Unique to this study, we found that males were enriched for inflammatory pathways and gene changes that suggested worse mitochondrial electron transport function while females were enriched for pathways related to mitochondrial homeostasis. Mitochondria isolated from the heart of males were confirmed to have worse mitochondrial respiration than females during myocarditis. Unbiased TRANSFAC analysis identified estrogen-related receptor alpha (ERRα) as a transcription factor that may mediate sex differences in mitochondrial function during myocarditis. Transcript and protein levels of ERRα were confirmed as elevated in females with myocarditis compared to males. Differential binding analysis from chromatin immunoprecipitation (ChIP) sequencing confirmed that ERRα bound highly to select predicted respiratory chain genes in females more than males during myocarditis. Conclusions Females with viral myocarditis regulate mitochondrial homeostasis by upregulating master regulators of mitochondrial transcription including ERRα.